(untitled) (World Marxist Review, 2026)
Mr. Enfu Cheng, the editor in chief of the book Methodology of Economics: a Perspective of Marx, Western Mainstream and Multidisciplines, and I have known each other for decades. A dozen years ago, when I showed my desire to promote international exchanges to the Marxist economist from China I knew, I asked who were the key figures in Marxist economics in China? Mr. Enfu Cheng was the answer. So, I invited him to make a speech at the commemoration of the founding of the JSPE (Japan Society of Political Economy), and we have been in touch ever since. Later, due to the establishment of the WAPE (World Association of Political Economy) in Shanghai, our communication has become even closer. I myself have always had the idea of establishing a Marxist association of political economy of Japan, China and South Korea, and I suggested it to Enfu Cheng. Unexpectedly, he replied, "This is a good ambition, but it is petty to limit it to China, Japan and South Korea. Our generation must create a world-class international society." After the establishment of the WAPE, as expected, it has achieved great development, which is proof enough that Enfu Cheng's proposal is superior to mine.